Simultaneous Confocal Scanning Laser Ophthalmoscopy Combined with High-Resolution Spectral-Domain Optical Coherence Tomography: A Review - Verônica Castro Lima; Eduardo B. Rodrigues; Renata P. Nunes; Juliana F. Sallum; Michel E. Farah; Carsten H. Meyer (Journal of Ophthalmology)
We aimed to evaluate technical aspects and the clinical relevance of a simultaneous confocal scanning laser ophthalmoscope and a high-speed, high-resolution, spectral-domain optical coherence tomography (SDOCT) device for retinal imaging. The principle of confocal scanning laser imaging provides a high resolution of retinal and choroidal vasculature with low light exposure. Enhanced contrast, details, and image sharpness are generated using confocality. The real-time SDOCT provides a new level of accuracy for assessment of the angiographic and morphological correlation. The combined system allows for simultaneous recordings of topographic and tomographic images with accurate correlation between them. Also it can provide simultaneous multimodal imaging of retinal pathologies, such as fluorescein and indocyanine green angiographies, infrared and blue reflectance (red-free) images, fundus autofluorescence images, and OCT scans (Spectralis HRA + OCT; Heidelberg Engineering, Heidelberg, Germany). The combination of various macular diagnostic tools can lead to a better understanding and improved knowledge of macular diseases.